Monitoring buried pipe deformation using acoustic emission: quantification of attenuation. Issue 4 (8th August 2017) - Smith, Alister; Dixon, Neil; Fowmes, Gary
Abstract : Deformation of soil bodies and soil-structure systems generates acoustic emission (AE), which are high-frequency stress waves. Listening to this AE by coupling sensors to structural elements can provide information on asset condition and early warning of accelerating deformation behaviour. There is a need for experimentation to model the propagation of AE in buried pipe systems to enhance understanding of real behaviour. Analytical solutions are often based on many assumptions (e.g. homogeneity, isotropy, boundary conditions and material properties) and cannot exactly represent the behaviour of the in situ system. This paper details a series of experiments conducted on buried pipes to investigate AE attenuation in pipes due to couplings and soil surround. The attenuation coefficients reported provide guidance to engineers for designing sensor spacing along buried pipes for monitoring ground deformations, and active waveguide installation depths for slope deformation monitoring. Attenuation coefficients have been quantified for both air–pipe–air and air–pipe–soil trilayer systems for the frequency range of 20–30 kHz.